NEW APPROACHES TO STABILIZE AQUEOUS SOOT SUSPENSIONS IN THE FIELD OF ULTRASOUND - Aleksandrova, Yulia; Budanova, Natalia; Zharova, Nelli; Okorokova, Nadezhda; Ustyuzhaninova, Galina; Farmakovskaya, Ariadna; Kohlert, Victoria (Revista Inclusiones, 2020)
In this work, we investigated the possibility of stabilization of aqueous low- and highly concentrated dispersed soot systems by diphilic high-molecular compounds. Based on the results, it can be concluded that the presence of hydrophobic fragments in the macromolecule chain plays a very significant role and positively affects the results of stabilization of aqueous soot dispersions. Studies have shown that the use of a stabilizer in combination with ultrasonic treatment of dispersed systems makes it possible to obtain stable homogeneous finely dispersed pastes. It was noted that a strong increase in the time and intensity of ultrasound processing of the system does not lead to a significant improvement in the results.